Increased Glycated Hemoglobin Levels in Patients With Helicobacter pylori Infection Are Associated With the Grading of Chronic Gastritis - Maluf, Selma; Salgado, João Victor; Cysne, Dalila Nunes; Camelo, Daniel Monte Freire; Nascimento, Johnny Ramos; Maluf, Bianca Vitória T.; Silva, Luís Douglas Miranda; Belfort, Marta Regina de Castro; Silva, Lucilene Amorim; Guerra, Rosane Nassar Meireles; Salgado Filho, Natalino; Nascimento, Flávia Raquel F. (Frontiers in Immunology, 2020)
Background: Recent studies have found an association between Helicobacter pylori infection and prediabetes. Whether H. pylori per se or host factors are involved in the disturbance of glycated hemoglobin needs further investigation. The aim of this study was to determine the association of glycated hemoglobin levels with endoscopic diagnosis and the inflammatory response in H. pylori infection. Methods: A cross-sectional study was carried out in 88 dyspeptic nondiabetic adults who underwent esophagogastroduodenoscopy. The diagnosis of H. pylori infection was performed through urease test and histopathological exam. Cases were initially distributed into two groups: control (without H. pylori infection, n=22) and HP (patients with H. pylori infection, n=66). HbA1c was measured to determine prediabetes status according to the American Diabetes Association criteria, and then the groups were subdivided into nonprediabetic (n=14), prediabetic (n= 8), nonprediabetic HP (n=26) and prediabetic HP (n=40) groups. Gastric mucosa was histologically evaluated to determine H. pylori density and inflammatory activity according to Sydney System. To investigate the balance of anti-inflammatory and pro-inflammatory cytokines we measured interleukin 10 (anti-inflammatory) and Tumor Necrosis Factor-a (pro-inflammatory) in the plasma or in the gastric mucosa. Results: Patients with H. pylori infection had higher mean HbA1c levels than those without H. pylori infection. However, increased HbA1c levels were not associated with H. pylori-related factors but with the bacterial density, the intensity of inflammation and the activity of the chronic gastritis. In addition, H. pylori infection per se did not alter IL-10 and TNF-α neither in the plasma nor in the gastric mucosa, but the bacterial density was negatively correlated with systemic and local IL-10 expression. Although no correlation was found between systemic cytokines and HbA1c levels, local anti-inflammatory cytokine was correlated with HbA1c levels. Conclusion: Long-term H. pylori infection is associated with prediabetes. This association is not related to the presence of H. pylori per se but depends on the extent of bacterial colonization and the degree of both local inflammation and activity of the chronic gastritis.